TOURISM COMPONENT DEVELOPMENT OF JAMBU TOURIST VILLAGE KAYENKIDUL DISTRICT KEDIRI REGENCY - Wulandari, Irawati; Meidiana, Christia; Prayitno, Gunawan (Department of Urban and Regional Planning, Faculty of Engineering, Universitas Brawijaya, 2025)
Tourist village is a rural area that has several special characteristics to become a tourist destination. The development of tourist villages has become an important strategy in strengthening the local economy, preserving cultural heritage, and improving the welfare of people in Indonesia, one of which is in Kediri Regency, East Java Province. Jambu Village is one of the villages and the only tourist village in Kayen Kidul District, Kediri Regency. Jambu Tourist Village is an independently managed tourist village, which has led this village to receive an award from the Governor of East Java as a Smart Mandiri Sejahtera Tourist Village (DEWI CEMARA) in October 2019. Despite its success, Jambu Tourist Village also experienced problems in its development process. Development of five tourism components (attraction, accessibility, accommodation, amenity, and ancillary) still faces many problems. The purpose of this study is to ensure sustainable tourism development by aligning the expectations of the community and visitors with the quality of service. Many issues remain persistent, particularly in the areas of public transportation, road infrastructure, and pedestrian facilities. To address these challenges, this study aims to measure the level of alignment between tourist satisfaction and the importance of various tourism components using the Importance-Performance Analysis (IPA) method. The results show a level of conformity of 68.97%, with 16 attributes falling into critical Quadrant I, indicating immediate priority for improvement. These results emphasize the need for strategic intervention to improve the overall quality of tourism services in Jambu Tourism Village.